Pengaruh Profitabilitas Dan Good Corporate Governance Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Rama Andi Wiguna; Muhammad Yusuf (ECONBANK: Journal of Economics and Banking, 2019)
This research aimed to get empirical evidence about the effect of profitability and good corporate governance as proxied by the proportion of independent board commissioners, number of board commissioners meetings, proportion of audit committee, number of audit committee meetings, managerial ownersip and institutional ownership. The population of this research was companies listed on the Indonesia Stock Exchange in 2016-2017. The sample of this research was fixed bypurposive sampling method so that was found 85 samples. Technique of data analysis was multiple linear regression. The result of research showed that profibility, the proportion of independent board commissioners, proporsion of audit committee, managerial ownership and institutional ownership had significant positive effect on firm value, while commissioners meetings and audit committee meetings had no effect on firm value.